2021
DOI: 10.3389/fimmu.2021.708472
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Microbiota in Infant Health: From Early Life to Adulthood

Abstract: From early life to adulthood, the microbiota play a crucial role in the health of the infant. The microbiota in early life are not only a key regulator of infant health but also associated with long-term health. Pregnancy to early life is the golden time for the establishment of the infant microbiota, which is affected by both environmental and genetic factors. Recently, there is an explosion of the studies on the role of microbiota in human diseases, but the application to disease or health is relatively limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
108
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(127 citation statements)
references
References 224 publications
(216 reference statements)
2
108
0
1
Order By: Relevance
“…Increasing number of research articles reported the important roles of gut microbiota in host energy and metabolism hemostasis ( Craig, 2004 ; Ejaz et al, 2016 ). During pregnancy to early life environment, maternal nutrient and microbiota contributed to the establishment of the infant microbiota and were associated with long-term health ( Yao et al, 2021 ). It certainly merits further exploration whether maternal betaine supplementation influences gut microbiota in both dams and offspring and therefore affects long-term health condition.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing number of research articles reported the important roles of gut microbiota in host energy and metabolism hemostasis ( Craig, 2004 ; Ejaz et al, 2016 ). During pregnancy to early life environment, maternal nutrient and microbiota contributed to the establishment of the infant microbiota and were associated with long-term health ( Yao et al, 2021 ). It certainly merits further exploration whether maternal betaine supplementation influences gut microbiota in both dams and offspring and therefore affects long-term health condition.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, certain bifidobacterial taxa cooperate with non-bifidobacterial taxa (including HMO consumers and non-HMO consumers) to maximize the nutrient consumption of HMOs, thus contributing to increased bifidobacterial diversity and dominance-gaining [ 29 ]. Considering the ability to digest HMOs, recent studies have confirmed that Lactobacillus , Bacteroides and Fragilis might also dominate the gut microbiota of infants to some extent [ 34 ]. Although other genera of neonatal intestinal microbiota (such as Clostridium , Enterococcus , Escherichia , Staphylococcus, and Streptococcus ) cannot degrade HMOs on their own, partial decomposition products or fermentation end-products might be produced in combination with Bifidobacterium and/or Bacteroides [ 35 , 36 ].…”
Section: What Are the ‘Infant-type’ Bifidobacterium ...mentioning
confidence: 99%
“…For example, the high-fat diet of breastfeeding mothers is linked to gut flora dysbiosis in their infants [ 49 ]. Before weaning, Bifidobacterium in the infant’s intestine gradually decreases due to competition from Bacteroides [ 34 ]. After weaning, bifidobacteria decrease, together with Clostridium perfringens and Clostridium difficile , while the abundance of other strictly anaerobic Clostridium increases [ 50 ].…”
Section: Establishment and Evolution Of Infant-type Bifidobacteriamentioning
confidence: 99%
“…The evolving field of the microbiome has revolutionized biomedical research in recent years, where it has emerged as an independent research specialty. In medicine, applied microbiome research offers new opportunities, including biomarker discovery, development of therapeutic targets, understanding of disparities in drug metabolization, and avenues for personalized medicine [ 1 ]. However, the complexities of the host–microbe ecological interactions hinder clinical transferability.…”
Section: Introductionmentioning
confidence: 99%
“…Different biomarkers are being tested in experimental studies, but only a few have been already integrated into clinical practice [ 7 ]. Today, the microbiome is envisioned as one of the most critical and hypothetically modifiable markers of disease [ 1 ].…”
Section: Introductionmentioning
confidence: 99%